Quantum dot-loaded layered double metal hydroxides, quantum dot glues and quantum dot films
By loading quantum dots on layered bimetallic hydroxide, the problems of quantum dot material stability and self-absorbing are solved, and higher chemical stability and photoconversion efficiency are achieved, reducing production costs.
Patent Information
- Application Number
- CN202411987010.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
Quantum dot materials have poor stability and are susceptible to oxygen and water vapor. High-concentration quantum dots may cause self-absorption in incremental membranes, wasting energy, limiting their application range.
By loading quantum dots onto layered bimetallic hydroxide, the quantum dots are protected using their structural characteristics and optical characteristics, delaying oxidation failure, and reducing the impact of the external environment through physical isolation, while reducing the concentration of quantum dots to reduce self-absorption.
It improves the chemical stability and environmental adaptability of quantum dots, reduces self-absorbing, improves light conversion efficiency, reduces energy waste, and reduces production costs.
Smart Images

Figure CN119752351A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of liquid crystal displays, and in particular to a quantum dot-loaded layered double metal hydroxide, quantum dot glue and a quantum dot film. Background Art
[0002] Quantum dots (QDs) are semiconductor nanocrystals with unique optical properties that enable them to emit light of different wavelengths when excited by a light source. This property stems from their ability to adjust the band structure due to their size. Quantum dot film technology replaces LED backlight modules by replacing phosphors in traditional components and using trillions of quantum dots protected by thin films to convert blue light into red and green light. This technology enables the quantum dot film to transmit more red, green, and blue light in the color filter than the white light emitted by traditional LEDs, enhancing the brightness and color richness of the display, and significantly improving the color gamut and color expression of LCD displays, such as increasing the color gamut from about 70% NTSC to more than 90%, or even more than 100%.
[0003] However, the stability of quantum dot materials cannot be ignored. They are easily affected by external environmental factors such as oxygen and water vapor, which limits their application in the display and lighting fields. In addition, multiple factors in the synthesis process of quantum dots lead to high raw material costs, and high concentrations of quantum dots may cause self-absorption in the incremental film, wasting energy, further limiting the scope of application of quantum dots.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] One of the purposes of the present invention is to provide a quantum dot-loaded layered double metal hydroxide, aiming to solve at least one of the above-mentioned technical problems in the prior art.
[0006] A second object of the present invention is to provide a quantum dot glue.
[0007] A third object of the present invention is to provide a quantum dot film.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] A first aspect of the present invention provides a quantum dot-loaded layered double metal hydroxide, wherein quantum dots are adsorbed on the surface of the layered double metal hydroxide;
[0010] The quantum dots include red quantum dots and / or green quantum dots;
[0011] The layered double metal hydroxide is a magnesium-aluminum layered double metal hydroxide;
[0012] The structure of the magnesium-aluminum layered double hydroxide is composed of regular octahedral MgO6 units, which together form a rhombus-shaped unit layer; part of the magnesium ions in the MgO6 units are replaced by aluminum ions; and anions are filled between every two unit layers.
[0013] Furthermore, the weight ratio of the layered double hydroxide to the quantum dots is 1:0.8-1.2.
[0014] Furthermore, the quantum dots include red quantum dots and green quantum dots.
[0015] The weight ratio of the red quantum dots to the green quantum dots is 0.2-1:0.2-1.
[0016] Furthermore, the red quantum dots include a semiconductor material with a core-shell structure, and the material of the quantum dots includes one or more of CdTe, CdSe, CdZnS, ZnSe, ZnO, ZnTe, GaN, GaAs, InP, InAs, AlSb, AlP, InSb, InN, etc. For example, the center is a CdSe core and the shell is ZnO. The wavelength of the quantum dots changes with the particle size;
[0017] Preferably, the green quantum dots include a semiconductor material with a core-shell structure, and the material of the quantum dots includes one or more of CdTe, CdSe, CdZnS, ZnSe, ZnO, ZnTe, GaN, GaAs, InP, InAs, AlSb, AlP, InSb, InN, etc. For example, the center is a CdSe core and the shell is ZnO. The wavelength of the quantum dots varies with the particle size.
[0018] The second aspect of the present invention provides a method for preparing the quantum dot-loaded layered double metal hydroxide, which comprises adding the layered double metal hydroxide to a quantum dot dispersion, mixing for 6 to 10 hours, filtering, washing, and drying to obtain the quantum dot-loaded layered double metal hydroxide.
[0019] Furthermore, in the quantum dot dispersion, the dispersion medium includes isobornyl acrylate, lauryl acrylate, cyclohexyl acrylate, methyl acrylate, ethyl acrylate, 2-ethylhexyl acrylate, n-butyl acrylate, and isodecyl acrylate.
[0020] Preferably, the mass percentage concentration of the quantum dot dispersion is 10-20wt%.
[0021] Furthermore, the mixing temperature is 60-80°C.
[0022] The third aspect of the present invention provides a quantum dot glue, comprising a resin glue and the layered double metal hydroxide loaded with quantum dots;
[0023] Wherein, the content of the layered double metal hydroxide loaded with quantum dots is 0.8-1.5%.
[0024] A fourth aspect of the present invention provides a quantum dot film, comprising a first barrier film, a quantum dot layer, and a second barrier film stacked in sequence;
[0025] The quantum dot layer is formed by curing the quantum dot glue.
[0026] Furthermore, the thickness of the quantum dot layer is 70-120 μm.
[0027] Compared with the prior art, the present invention has at least the following beneficial effects:
[0028] The layered double metal hydroxide loaded with quantum dots provided by the present invention loads quantum dots onto the layered double metal hydroxide by means of intercalation and adsorption, and utilizes the structural characteristics and optical features of the layered double metal hydroxide to protect the intercalated and adsorbed quantum dots, thereby delaying the oxidation failure of the quantum dots. This structure not only provides a stable environment for the quantum dots, reducing the influence of the external environment such as oxygen and water vapor on their stability, but also physically isolates the quantum dots from direct contact with the outside world, thereby improving the environmental adaptability and chemical stability of the quantum dots. The layered double metal hydroxide replaces the scattering particles of the original formula, effectively reducing the concentration of quantum dots, thereby reducing the self-absorption phenomenon caused by high-concentration quantum dots in the incremental film. By reducing the concentration of quantum dots, the interaction and self-absorption between quantum dots are reduced, the light conversion efficiency is improved, and the problem of energy waste due to absorption of photons caused by high concentration is also reduced.
[0029] The preparation method provided by the present invention has easy-to-obtain raw materials, a simple process synthesis route, and a low-cost advantage. In addition, under high temperature and high humidity environments, the optical properties and appearance of the quantum dot film are significantly improved, thereby enhancing the environmental adaptability and stability of the material.
[0030] The quantum dot glue provided by the present invention, in view of the advantages of the above-mentioned layered double metal hydroxide loaded with quantum dots, enables the prepared quantum dot glue to have a lower concentration of quantum dots, reduce production costs, and at the same time improve the self-absorption phenomenon of quantum dots in the quantum dot film, thereby improving the light conversion efficiency.
[0031] The quantum dot film provided by the present invention has the advantages of high color gamut coverage, high color purity, long-lasting and stable color, and low power consumption. In addition, the present invention improves the service life and performance stability of the quantum dot film by enhancing the protection network of the quantum dots, while ensuring high reliability and low failure margin, which is suitable for the needs of future borderless design. This technical solution enables the quantum dot film to have significant application advantages and broad market prospects in the field of display technology. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0033] Figure 1 A schematic diagram of the structure of a layered double metal hydroxide loaded with quantum dots provided by the present invention;
[0034] Figure 2 A schematic diagram of the structure of the quantum dot film provided by the present invention;
[0035] Figure 3 This is a spectrum comparison chart obtained in Test Example 2.
[0036] Icons: 101 - first PET substrate layer; 102 - first inorganic barrier layer; 103 - second PET substrate layer; 104 - second inorganic barrier layer; 105 - quantum dot layer; 106 - red quantum dots; 107 - green quantum dots. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0038] Hereinafter, the terms "including", "having" and their cognates, which may be used in various embodiments of the present invention, are intended only to indicate specific features, numbers, steps, operations, elements, components or combinations of the foregoing items, and should not be understood as first excluding the existence of one or more other features, numbers, steps, operations, elements, components or combinations of the foregoing items or adding the possibility of one or more features, numbers, steps, operations, elements, components or combinations of the foregoing items.
[0039] The first aspect of the present invention provides a quantum dot-loaded layered double metal hydroxide, the structural schematic diagram of which is shown in FIG. Figure 1Said, quantum dots are adsorbed on the surface of the layered double metal hydroxide;
[0040] The quantum dots include red quantum dots and / or green quantum dots;
[0041] The layered double metal hydroxide is a magnesium-aluminum layered double metal hydroxide;
[0042] The structure of the magnesium-aluminum layered double hydroxide is composed of regular octahedral MgO6 units, which together form a rhombus-shaped unit layer; part of the magnesium ions in the MgO6 units are replaced by aluminum ions; and anions are filled between every two unit layers.
[0043] The layered double metal hydroxide loaded with quantum dots provided by the present invention loads quantum dots onto the layered double metal hydroxide by means of intercalation and adsorption, and utilizes the structural characteristics and optical features of the layered double metal hydroxide to protect the intercalated and adsorbed quantum dots, thereby delaying the oxidation failure of the quantum dots. This structure not only provides a stable environment for the quantum dots, reducing the influence of the external environment such as oxygen and water vapor on their stability, but also physically isolates the quantum dots from direct contact with the outside world, thereby improving the environmental adaptability and chemical stability of the quantum dots. The layered double metal hydroxide replaces the scattering particles of the original formula, effectively reducing the concentration of quantum dots, thereby reducing the self-absorption phenomenon caused by high-concentration quantum dots in the incremental film. By reducing the concentration of quantum dots, the interaction and self-absorption between quantum dots are reduced, the light conversion efficiency is improved, and the problem of energy waste due to absorption of photons caused by high concentration is also reduced.
[0044] Furthermore, the weight ratio of the layered double hydroxide to the quantum dots is 1:0.8-1.2.
[0045] Furthermore, the quantum dots include red quantum dots and green quantum dots.
[0046] The weight ratio of the red quantum dots to the green quantum dots is 0.2-1:0.2-1.
[0047] Furthermore, the red quantum dots include a semiconductor material with a core-shell structure, and the material of the quantum dots includes one or more of CdTe, CdSe, CdZnS, ZnSe, ZnO, ZnTe, GaN, GaAs, InP, InAs, AlSb, AlP, InSb, InN, etc. For example, the center is a CdSe core and the shell is ZnO. The wavelength of the quantum dots changes with the particle size;
[0048] Preferably, the green quantum dots include a semiconductor material with a core-shell structure, and the material of the quantum dots includes one or more of CdTe, CdSe, CdZnS, ZnSe, ZnO, ZnTe, GaN, GaAs, InP, InAs, AlSb, AlP, InSb, InN, etc. For example, the center is a CdSe core and the shell is ZnO. The wavelength of the quantum dots varies with the particle size.
[0049] The second aspect of the present invention provides a method for preparing the quantum dot-loaded layered double metal hydroxide, which comprises adding the layered double metal hydroxide to a quantum dot dispersion, mixing for 6 to 10 hours, filtering, washing, and drying to obtain the quantum dot-loaded layered double metal hydroxide.
[0050] The preparation method provided by the present invention has easy-to-obtain raw materials, a simple process synthesis route, and a low-cost advantage. In addition, under high temperature and high humidity environments, the optical properties and appearance of the quantum dot film are significantly improved, thereby enhancing the environmental adaptability and stability of the material.
[0051] Furthermore, the preparation method of the layered double hydroxide includes: mixing a certain proportion of magnesium nitrate hexahydrate and aluminum nitrate nonahydrate powder and dissolving them uniformly in deionized water to prepare a salt solution; taking another certain amount of sodium hydroxide and sodium carbonate and dissolving them uniformly in deionized water to prepare a salt solution, under a nitrogen protection environment, the two salt solutions are uniformly added dropwise to the deionized water, the pH value of the solution is controlled to be constant, and a certain amount of formamide is added, refluxed at a certain temperature for crystallization for 12 hours, the obtained colloidal precipitate is washed with water to pH = 7, and dried at 65°C for 12 hours to obtain MgAl-LDH powder.
[0052] Preferably, the molar ratio of magnesium nitrate hexahydrate to aluminum nitrate nonahydrate powder is 1 to 4:1.
[0053] Preferably, magnesium nitrate hexahydrate and aluminum nitrate nonahydrate powders are mixed and uniformly dissolved in deionized water to prepare a salt solution with a total concentration of 0.1 to 1 mol / L.
[0054] Preferably, the molar ratio of sodium hydroxide to sodium carbonate powder is 6 to 10:1.
[0055] Preferably, sodium hydroxide and sodium carbonate are uniformly dissolved in deionized water to prepare a salt solution with a total concentration of 1-3 mol / L.
[0056] Preferably, the pH value of the solution is controlled to be constant in the range of 8-11, and needs to be adjusted using 1 mol / L NaOH solution.
[0057] Preferably, the added amount of formamide accounts for 1-10 wt % of the total solution content.
[0058] Preferably, the reflux crystallization temperature needs to be controlled at 60-75°C.
[0059] Furthermore, in the quantum dot dispersion, the dispersion medium includes isobornyl acrylate, lauryl acrylate, cyclohexyl acrylate, methyl acrylate, ethyl acrylate, 2-ethylhexyl acrylate, n-butyl acrylate, and isodecyl acrylate.
[0060] Preferably, the mass percentage concentration of the quantum dot dispersion is 10-20wt%.
[0061] Furthermore, the mixing temperature is 60-80°C.
[0062] The third aspect of the present invention provides a quantum dot glue, comprising a resin glue and the layered double metal hydroxide loaded with quantum dots;
[0063] Wherein, the content of the layered double metal hydroxide loaded with quantum dots is 0.8-1.5%.
[0064] The quantum dot glue provided by the present invention, in view of the advantages of the above-mentioned layered double metal hydroxide loaded with quantum dots, enables the prepared quantum dot glue to have a lower concentration of quantum dots, reduce production costs, and at the same time improve the self-absorption phenomenon of quantum dots in the quantum dot film, thereby improving the light conversion efficiency.
[0065] A fourth aspect of the present invention provides a quantum dot film, comprising a first barrier film, a quantum dot layer, and a second barrier film stacked in sequence;
[0066] The quantum dot layer is formed by curing the quantum dot glue.
[0067] The quantum dot film provided by the present invention has the advantages of high color gamut coverage, high color purity, long-lasting and stable color, and low power consumption. In addition, the present invention improves the service life and performance stability of the quantum dot film by enhancing the protection network of the quantum dots, while ensuring high reliability and low failure margin, which is suitable for the needs of future borderless design. This technical solution enables the quantum dot film to have significant application advantages and broad market prospects in the field of display technology.
[0068] In one embodiment of the present invention, the schematic structural diagram of the quantum dot film is as follows: Figure 2 As shown, it includes a first PET substrate layer 101, a first inorganic barrier layer 102, a quantum dot layer 105, a second inorganic barrier layer 104 and a second PET substrate layer 103 which are stacked, and the quantum dot layer 105 contains red quantum dots 106 and green quantum dots 107.
[0069] Furthermore, the thickness of the quantum dot layer is 70-120 μm.
[0070] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.
[0071] Example 1
[0072] This embodiment provides a quantum dot-loaded layered double hydroxide QD-LDH, and the preparation process is as follows:
[0073] 1. Mix magnesium nitrate hexahydrate (12.8 g, 0.05 mol) and aluminum nitrate nonahydrate (18.8 g, 0.05 mol) powders and dissolve them in 100 mL of deionized water to prepare a salt solution; separately, take sodium hydroxide (0.2 mol) and sodium carbonate (0.025 mol) and dissolve them in 100 mL of deionized water to prepare a salt solution. Under nitrogen protection, the two salt solutions are uniformly added dropwise to the deionized water, the pH of the solution is controlled to 10, and 2 g of formamide is added. Reflux crystallization is carried out at 65° C. for 12 h, the obtained colloidal precipitate is washed with water to pH = 7, and dried at 65° C. for 12 h to obtain MgAl-LDH powder with a yield of about 81%.
[0074] 2. 100 mL of quantum dot dispersion (15 wt %, Nanosys, USA) was fully mixed with 20 g of MgAl-LDH, stirred at 70° C. for 7 h, filtered and washed, and vacuum dried for 24 h to obtain a layered double hydroxide loaded with quantum dots, with a loading rate of 85%.
[0075] Example 2
[0076] The present embodiment provides a quantum dot-loaded layered double hydroxide QD-LDH. The difference from Example 1 is that in step 1, magnesium nitrate hexahydrate (16.9 g, 0.066 mol) and aluminum nitrate nonahydrate (11.4 g, 0.033 mol) powders are evenly mixed and dissolved in 100 mL of deionized water to form a salt solution. The remaining steps are the same as in Example 1 and are not repeated here.
[0077] Example 3
[0078] The present embodiment provides a quantum dot-loaded layered double hydroxide QD-LDH. The difference from Example 1 is that in step 1, magnesium nitrate hexahydrate (19.2 g, 0.075 mol) and aluminum nitrate nonahydrate (9.4 g, 0.025 mol) powders are evenly mixed and dissolved in 100 mL of deionized water to form a salt solution. The remaining steps are the same as in Example 1 and are not repeated here.
[0079] Example 4
[0080] This embodiment provides a quantum dot-loaded layered double hydroxide QD-LDH, and the preparation process is as follows:
[0081] 1. Mix magnesium nitrate hexahydrate (19.2 g, 0.075 mol) and aluminum nitrate nonahydrate (9.4 g, 0.025 mol) powders and dissolve them in 100 mL of deionized water to prepare a salt solution; separately, take sodium hydroxide (0.2 mol) and sodium carbonate (0.025 mol) and dissolve them in 100 mL of deionized water to prepare a salt solution. Under nitrogen protection, the two salt solutions are uniformly added dropwise to the deionized water, the pH of the solution is controlled to 8, and 2 g of formamide is added. Reflux crystallization is carried out at 65° C. for 12 hours, the obtained colloidal precipitate is washed with water to pH = 7, and dried at 65° C. for 12 hours to obtain MgAl-LDH powder with a yield of about 89%.
[0082] 2. Fully mix 100 mL of quantum dot dispersion (15 wt %, Nanosys, USA) with 20 g of MgAl-LDH, stir at 70° C. for 7 h, filter and wash, and vacuum dry for 24 h to obtain a layered double hydroxide loaded with quantum dots, with a loading rate of 80%.
[0083] Example 5
[0084] This embodiment provides a quantum dot-loaded layered double hydroxide QD-LDH, and the preparation process is as follows:
[0085] 1. Mix magnesium nitrate hexahydrate (19.2 g, 0.075 mol) and aluminum nitrate nonahydrate (9.4 g, 0.025 mol) powders and dissolve them in 100 mL of deionized water to prepare a salt solution; separately, take sodium hydroxide (0.2 mol) and sodium carbonate (0.025 mol) and dissolve them in 100 mL of deionized water to prepare a salt solution. Under nitrogen protection, the two salt solutions are uniformly added dropwise to the deionized water, the pH of the solution is controlled to 9, and 2 g of formamide is added. Reflux crystallization is carried out at 65° C. for 12 hours. The obtained colloidal precipitate is washed with water to pH = 7, and dried at 65° C. for 12 hours to obtain MgAl-LDH powder with a yield of about 93%.
[0086] 2. 100 mL of quantum dot dispersion (15 wt %, Nanosys, USA) was fully mixed with 20 g of MgAl-LDH, stirred at 70° C. for 7 h, filtered and washed, and vacuum dried for 24 h to obtain a layered double hydroxide loaded with quantum dots, with a loading rate of 84%.
[0087] Example 6
[0088] This embodiment provides a quantum dot-loaded layered double hydroxide QD-LDH, and the preparation process is as follows:
[0089] 1. Mix magnesium nitrate hexahydrate (19.2 g, 0.075 mol) and aluminum nitrate nonahydrate (9.4 g, 0.025 mol) powders and dissolve them in 100 mL of deionized water to prepare a salt solution; separately, take sodium hydroxide (0.2 mol) and sodium carbonate (0.025 mol) and dissolve them in 100 mL of deionized water to prepare a salt solution. Under nitrogen protection, the two salt solutions are uniformly added dropwise to the deionized water, the pH of the solution is controlled to 11, and 2 g of formamide is added. Reflux crystallization is carried out at 65° C. for 12 hours, the obtained colloidal precipitate is washed with water to pH = 7, and dried at 65° C. for 12 hours to obtain MgAl-LDH powder with a yield of about 97%.
[0090] 2. Fully mix 100 mL of quantum dot dispersion (15 wt %, Nanosys, USA) with 20 g of MgAl-LDH, stir at 70° C. for 7 h, filter and wash, and vacuum dry for 24 h to obtain a layered double metal hydroxide loaded with quantum dots, with a loading rate of 95%.
[0091] Embodiments 7 to 12
[0092] This embodiment provides a quantum dot film, and the preparation process is as follows:
[0093] 1. Weigh 15 g of the QD-LDH obtained in Examples 1 to 6 and dissolve it again in 85 mL of IBOA to obtain a QD-LDH dispersion.
[0094] 2. Take 10g of QD-LDH dispersion and 100g of acrylic ester glue formula and stir it with a mechanical rotor at 65°C for 2h to obtain a uniformly dispersed quantum dot glue.
[0095] 3. Inject the evenly dispersed quantum dot glue into the die head through a peristaltic pump, and use the composite film preparation process to evenly coat the quantum dot glue on two PET barrier films (water vapor barrier rate less than 0.1g / (m 2 *24h)), firstly it is pressed by gap rollers, and then it is cured by high-pressure UV lamp to obtain a quantum dot membrane. The thickness of the quantum dot membrane glue layer is 100 microns, and the thickness of the quantum dot membrane is 320 microns.
[0096] Comparative Example 1
[0097] This comparative example provides a quantum dot film, and the preparation process is as follows:
[0098] 1. Take 10g of 15% quantum dot dispersion (15wt%, Nanosys, USA) and 100g of acrylic glue formula and stir with a mechanical rotor at 65°C for 2h to obtain a uniformly dispersed quantum dot glue.
[0099] 2. The evenly dispersed quantum dot glue is injected into the die head through a peristaltic pump. The composite film preparation process is used to evenly coat the quantum dot glue between two PET barrier films. First, it is pressed by a gap roller and then cured by a high-pressure UV lamp to obtain a quantum dot membrane. The thickness of the quantum dot membrane glue layer is 100 microns and the thickness of the quantum dot membrane is 320 microns.
[0100] Test Example 1
[0101] The yield of LDH, QD-LDH loading rate and QD-LDH solubility obtained in Examples 1 to 6 were statistically analyzed.
[0102] 1. Yield of layered double hydroxide: Yield = total mass of product after reaction / sum of mass of input materials before each reaction.
[0103] 2. Loading rate of QD-LDH: Loading rate = mass of layered double hydroxide loaded with quantum dots / (mass of input quantum dots + mass of input layered double hydroxide).
[0104] 3. Observation of the dispersion stability of QD-LDH: QD-LDH dispersion was added to the acrylic glue system, heated and stirred at 65°C for 2 hours, then allowed to stand and the sedimentation was observed.
[0105] The results are shown in Table 1 below.
[0106] Table 1
[0107] Yield % Load rate % Dispersibility Example 1 81 85 No sedimentation Example 2 88 91 No sedimentation Example 3 98 95 No sedimentation Example 4 89 80 No sedimentation Example 5 93 84 No sedimentation Example 6 97 95 No sedimentation
[0108] As shown in Table 1, magnesium aluminum layered double hydroxide can be well dispersed in the glue system under different feed ratios and different pH environments. In addition, in Examples 2 and 6, a higher yield and a higher loading rate for quantum dots are shown.
[0109] Test Example 2
[0110] The optical data of the quantum dot films obtained in Examples 7 to 12 and Comparative Example 1 were tested before being put into aging test.
[0111] 1. Quantum dot film white field color coordinates (Wx, Wy) and brightness (Lv / nits) performance test: Place an A4-sized quantum dot film at the center of a backlight module with a blue light wavelength of 446nm. Take a double-layer composite brightness enhancement film with prisms perpendicular to each other and cover it on the quantum dot film as the optical structure of the module. Use a luminance meter (CS-2000) to perform an optical performance test at a distance of 1 meter from the center of the quantum dot film to obtain the white field color coordinates and brightness data of the quantum dot film.
[0112] 2. Quantum film wavelength (nm) and half-peak width (nm) performance test: Place an A4-sized quantum dot film in the center of a backlight module with a blue light wavelength of 446nm, take a double-layer composite brightening film with prisms perpendicular to each other and cover it on the quantum dot film as the optical architecture of the module, use a luminance meter (CS-2000) to perform an optical performance test at a center position 1 meter away from the quantum dot film, and obtain the optical data spectrum of the quantum dot film in the range of 380-780nm. Then import the spectrum into the origin software for calculation, and you can get the peak wavelength and half-peak width data of the red quantum dots in the quantum dot film and the peak wavelength and half-peak width data of the green quantum dots.
[0113] The obtained results are shown in Table 2 below.
[0114] Table 2
[0115]
[0116] It can be seen from Table 2 that there is no significant difference in the brightness, white field color coordinates (Wx, Wy), half-width of the quantum dots (FWHM) and wavelength (peak) of the quantum dots among the six groups of embodiment and control example films, indicating that loading the quantum dots on the layered double metal hydroxide has no significant effect on the optical properties of the quantum dots.
[0117] Figure 3 This is a spectrum comparison diagram of the quantum dot film obtained in Example 9 and Comparative Example 1. The curves can further illustrate that the layered double metal hydroxide has no effect on the quantum dots.
[0118] Test Example 3
[0119] The optical data changes of the quantum dot films obtained in Examples 7 to 12 and Comparative Example 1 after being subjected to a high temperature and high humidity (65° C., 95% rh) aging test for 1000 hours were compared.
[0120] 1. Film surface aging resistance test: Place the A4-sized quantum dot film in an aging test oven at 65°C and 95% RH for 1000 hours. Test the white field color coordinates and brightness data of the quantum dot film before and after aging, and compare the optical performance loss after aging.
[0121] 2. Observation of failure points on the film surface: Take out the quantum dot film after the aging test, place the quantum dot film in the center of the backlight module with a blue light wavelength of 446nm, take a double-layer composite brightening film with prisms perpendicular to each other and cover it on the quantum dot film as the optical structure of the module, wear anti-blue light glasses to observe the quantum dot film, if dark blue spots are visible, it is judged to be a serious failure; if there is no abnormality, it is necessary to remove the structure for observation, if dark blue spots are visible, it is judged to be a slight failure; if there is no failure point, it is judged that the film has not failed.
[0122] The results are shown in Table 3 below.
[0123] Table 3
[0124] △Lv △x △y Membrane failure point Failure edge of membrane surface / mm Example 7 -5.40% -0.0046 -0.0061 Minor failure point across the entire width 0.8 Example 8 -4.96% -0.0032 -0.0042 Minor failure point across the entire width 1.0 Example 9 -5.39% -0.0042 -0.0045 No failure points 0.2 Example 10 -5.79% -0.0043 -0.0060 Slight failure point across the entire width 0.5 Embodiment 11 -5.78% -0.0052 -0.0058 Minor failure point across the entire width 0.2 Example 12 -5.37% -0.0042 -0.0062 No failure points 0.2 Comparative Example 1 -9.03% -0.0063 -0.0078 Full-width obvious failure point 1.5
[0125] In Table 3, △Lv = (brightness after RA - brightness before RA) / brightness before RA; △x = Wx after RA - Wx before RA; △y = Wy after RA - Wy before RA. By loading quantum dots on layered double hydroxides, not only the uniformity of quantum dots in the film is promoted, but also the problem of large attenuation of optical properties of quantum dot films after high temperature and high humidity aging can be effectively improved, and the stability of quantum dots in the polyacrylic acid glue system is improved. And when selecting the appropriate feed ratio and pH conditions, it is beneficial to improve the yield and loading rate of layered double hydroxides, and can show more excellent optical properties.
[0126] Finally, it should be noted that the above-described embodiments are only specific implementations of the present invention, which are used to illustrate the technical solutions of the present invention, rather than to limit them. The protection scope of the present invention is not limited thereto. Although the present invention is described in detail with reference to the above-described embodiments, ordinary technicians in the field should understand that any technician familiar with the technical field can still modify the technical solutions recorded in the above-described embodiments within the technical scope disclosed by the present invention, or can easily think of changes, or make equivalent replacements for some of the technical features therein; and these modifications, changes or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention, and should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.
Claims
1. A quantum dot-loaded layered double metal hydroxide, characterized in that: Quantum dots are adsorbed on the surface of the layered double hydroxide; The quantum dots include red quantum dots and / or green quantum dots; The layered double metal hydroxide is a magnesium-aluminum layered double metal hydroxide; The structure of the magnesium-aluminum layered double hydroxide is composed of regular octahedral MgO6 units, which together form a rhombus-shaped unit layer; part of the magnesium ions in the MgO6 units are replaced by aluminum ions; and anions are filled between every two unit layers.
2. The quantum dot-loaded layered double hydroxide according to claim 1, characterized in that: The weight ratio of the layered double metal hydroxide to the quantum dots is 1:0.8-1.
2.
3. The quantum dot-loaded layered double hydroxide according to claim 1, characterized in that: The quantum dots include red quantum dots and green quantum dots; The weight ratio of the red quantum dots to the green quantum dots is 0.2-1:0.2-1.
4. The quantum dot-loaded layered double hydroxide according to any one of claims 1 to 3, characterized in that: The red quantum dots include a semiconductor material with a core-shell structure, and the material of the quantum dots includes one or more of CdTe, CdSe, CdZnS, ZnSe, ZnO, ZnTe, GaN, GaAs, InP, InAs, AlSb, AlP, InSb, and InN; Preferably, the green quantum dots include a semiconductor material with a core-shell structure, and the material of the quantum dots includes one or more of CdTe, CdSe, CdZnS, ZnSe, ZnO, ZnTe, GaN, GaAs, InP, InAs, AlSb, AlP, InSb, and InN.
5. A method for preparing a quantum dot-loaded layered double metal hydroxide according to any one of claims 1 to 4, characterized in that: The layered double metal hydroxide is added to the quantum dot dispersion, and then mixed for 6 to 10 hours, filtered, washed, and dried to obtain the layered double metal hydroxide loaded with quantum dots.
6. The preparation method according to claim 5, characterized in that: In the quantum dot dispersion, the dispersion medium includes isobornyl acrylate, lauryl acrylate, cyclohexyl acrylate, methyl acrylate, ethyl acrylate, 2-ethylhexyl acrylate, n-butyl acrylate, and isodecyl acrylate; Preferably, the mass percentage concentration of the quantum dot dispersion is 10-20wt%.
7. The preparation method according to claim 5, characterized in that: The mixing temperature is 60-80°C.
8. A quantum dot glue, characterized in that: A layered double metal hydroxide comprising resin glue and the quantum dot-loaded layered double metal hydroxide according to any one of claims 1 to 4; Wherein, the content of the layered double metal hydroxide loaded with quantum dots is 0.8-1.5%.
9. A quantum dot film, characterized in that: It includes a first barrier film, a quantum dot layer and a second barrier film which are stacked in sequence; The quantum dot layer is formed by curing the quantum dot glue described in claim 8.
10. The quantum dot film according to claim 9, characterized in that: The thickness of the quantum dot layer is 70-120 μm.